Yamuna Kachru's contribution to linguacultural studies. Issue 1 (March 2015) - PROSHINA, ZOYA G.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT This paper summarizes the major theses Professor Yamuna Kachru developed in the field of linguaculture: the relations between language and culture, role of English diversity in enriching speaker's worldview, dependence of language dynamics on the change of the sociocultural context; cultural specifics of text types; the culture's effects on cognition; impact of social conventions and linguistic strategies on intercultural communication, and role of contact literature in enriching English user's background knowledge. All these arguments serve as a solid basis for the world Englishes paradigm closely associated with intercultural communication studies.